Research on the Effect of Diversified Cropping on Crop Quality: A Review - Hong Fan; Rong Miao; Congcong Guo; Xiaoyuan Bao; Wei He; Yali Sun; Cai Zhao (Agriculture)
Diversified cropping, as a crucial measure in modern ecological agriculture, promotes the intensification, industrialization, and diversification of agricultural production. By addressing region-specific and environmental challenges, the development of diversified cropping systems (DCS) tailored to local conditions can achieve the dual goals of improving crop quality and ensuring food security. However, existing crop quality improvement research primarily focuses on molecular techniques, with limited exploration of cropping practices. This review aims to systematically and comprehensively examine the concept, classification, and significance of diversified cropping. It highlights the critical roles and mechanisms of various cropping systems, such as intercropping, crop rotation, relay cropping, and multiple cropping, in enhancing crop quality. Furthermore, the review discusses the limitations and challenges of diversified cropping and offers suggestions for its improvement and application to advance research in this field. By proposing a scientific framework linking DCS with crop quality improvement, this review contributes to the formulation of evidence-based agricultural strategies to meet the growing demand for high-quality food, maintain environmental health, and promote long-term agricultural sustainability.